COVID-19 vaccination attitudes and intention among Quebecers during the first and second waves of the pandemic: findings from repeated cross-sectional surveys. Issue 11 (2nd November 2021) - Dubé, Ève; Dionne, Maude; Pelletier, Catherine; Hamel, Denis; Gadio, Souleymane
ABSTRACT: The availability of safe and effective vaccines is a major breakthrough in controlling the COVID-19 pandemic. However, the success of the COVID-19 vaccination campaign relies on high uptake by the public. We monitored Quebecers' attitudes and intention toward COVID-19 vaccination during the first and second waves of the pandemic. Since March 2020, online surveys are conducted every week in Quebec (Canada) to assess Quebecers' adherence to recommended public health measures (3, 300 respondents are surveyed every week through an online panel; respondents are not invited to answer the survey for 21 days after responding). Ten items measured respondents' attitudes and intentions regarding COVID-19 vaccination. Logistic regression models were used to identify determinants of intention to be vaccinated against COVID-19. Intention to be vaccinated against COVID-19 ranged from 76%-66% between the first and second waves. The proportion of undecided adults remained stable (12%). Being a man; being 60 years of age and over; having a university education level; having or living with someone with chronic medical conditions and increased risk perceptions of COVID-19 were the strongest predictors of COVID-19 vaccine acceptance in multivariate analysis. During data collection, COVID-19 vaccine supply was very limited. It was reassuring to note that intention to be vaccinated is the highest among older age groups that are prioritized to be vaccinated first. As more doses and vaccines will be available it will be important to enhance vaccine acceptance and uptake, especially among adults younger than 60 years of age and Quebecers with lower risk perceptions of COVID-19.